Globalization and the Cultural/Creative Industries: An Assessment of Nigeria’s Position in the Global Space (Journal of Advanced Research in Social Sciences, 2019)
This study provides an assessment of globalization and its impact on top performing creative industries in Nigeria. The prospects and contributions of the Nigerian film, music and fashion industries to the Gross Domestic Product (GDP) were highlighted in a bid to position Nigeria in the global creative space. The study adopted cognitive capitalism as its theoretical framework, and the role of culture as the major product of cognitive capitalism was explored as solutions for developing the Nigerian creative space. Empirical studies by leading research organizations and relevant agencies focused on analyzing the contributions of different sectors of the economy to national growth were reviewed. A review of secondary data indicates that the contributions of Nigeria’s creative industries to the global scale is on the rise. Factors that determine Nigeria’s role were obtained from secondary sources and were used to form the basis for the conclusions drawn by the study.